Effectiveness of continuous passive motion device in postoperative anterior acromioplasty rehabilitation [Anteri̇or akromi̇yoplasti̇ sonrasi rehabi̇li̇tasyonda sürekli̇ pasi̇f hareket ci̇hazinin etki̇nli̇ǧ i̇] - (:unkn) unknown (My University, 2002)
Thirty patients who underwent anterior acromioplasty procedure, and referred for rehabilitation from The Department of Orthopedic Surgery to The Department of Physical Medicine and Rehabilitation (PM&R) between October 1999-July 2001, were included in the study in order to investigate the early and delayed effects of continuous passive motion (CPM) device of the shoulder. Patients were randomly divided into two groups and the first group received a conventional rehabilitation program applied routinely in our PM&R clinic starting from the second day of operation. The components to increase range of motion of this program consisted of passive exercises applied manually by the physical therapist in the first postoperative week, and active-assisted exercises beginning in the second week. The second group was given all components of the conventional program, except range of motion exercises. Shoulder elevation and rotations in three planes were performed by means of a CPM device in this latter group. The duration of treatment for both groups was three months. All patients were assessed with goniometric range of motion measurements (passive and active), pain (visual analogue scale, face scale), simple shoulder test, Constant Shoulder Score, and use of antiinflammatory medications, before the rehabilitation program, and after 4, and 12 weeks. It is concluded that shoulder rehabilitation with CPM device has no preference on patients who had anterior acromiyoplasty operation in comparison with the conventional method, and both of the methods were similarly beneficial.
Keywords: Anterior acromioplasty; Continuous passive motion; Rehabilitation; Shoulder; Subacromial impingement syndrome